Exchanging Experience with Conservation Agriculture : Towards Climate Resilience - Li, Hongwen; Xie, Mei; He, Jin (Popular Sciene Press and The World Bank, 2014)
This booklet offers advice for farmers and extension workers interested in using conservation agriculture techniques to boost crop yields, soil quality and water retention. These practices represent some of the many ways we can become more climate smart, which is essential if we are to sustainably produce more food on less land to feed our growing planet.